An inconsistent policy: lifelong learning and adult education policy towards a competitive advantage - Guimarães, Paula (2018)
This chapter focuses on the ways by which EU lifelong learning agenda, specifically the guidelines for basic skills, has been interpreted according to the Portuguese realities, at national and local levels. We suggest that basic skills for all, as intended in the framework of the European area of lifelong learning, have somewhat loose roots on the cultural and civic dimensions of education in a human and social development perspective. Competitiveness and social cohesion, the dual centrality of lifelong education and learning for Europe, stated in Lisbon Strategy, have been interpreted and translated in Portugal through a dynamic imbalanced agenda fed by two major strands: the prosecution of a social right for a long time in debt to adult population and a search for so-called employability and qualification, as a way to tackle Portuguese distance from European educational standards. According to these options that frame the EU agenda, this chapter also stresses the adults’ understandings of adult education which come out from the research findings presented later. The data analysis shows that these understandings are congruent with EU orientations; adults see adult education as a promise of a better life. Thus, given the inconsistency of lifelong learning, fulfilling this promise is a hard task to achieve.